2018
DOI: 10.1007/s00268-017-4420-x
|View full text |Cite
|
Sign up to set email alerts
|

Early Management of Retained Hemothorax in Blunt Head and Chest Trauma

Abstract: BackgroundMajor blunt chest injury usually leads to the development of retained hemothorax and pneumothorax, and needs further intervention. However, since blunt chest injury may be combined with blunt head injury that typically requires patient observation for 3–4 days, other critical surgical interventions may be delayed. The purpose of this study is to analyze the outcomes of head injury patients who received early, versus delayed thoracic surgeries.Materials and methodsFrom May 2005 to February 2012, 61 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 22 publications
(35 reference statements)
1
13
2
2
Order By: Relevance
“…Other studies have usually targeted treatments of severe blunt chest trauma by managing the hemothorax or pneumothorax [21][22][23]. Initially, fractured ribs were not the main target of treatment in our hospital [23].…”
Section: Discussionmentioning
confidence: 97%
“…Other studies have usually targeted treatments of severe blunt chest trauma by managing the hemothorax or pneumothorax [21][22][23]. Initially, fractured ribs were not the main target of treatment in our hospital [23].…”
Section: Discussionmentioning
confidence: 97%
“…Chấn thương ngực (CTN) là một cấp cứu ngoại khoa thường gặp ở các bệnh viện lớn của tỉnh và thành phố, chiếm khoảng 7-10% cấp cứu ngoại khoa 1,2 . Chấn thương ngực là thương tích phổ biến thứ ba ở bệnh nhân chấn thương, sau chấn thương đầu và tứ chi, tỷ lệ tử vong là 10,8%.…”
Section: đặT Vấn đềunclassified
“…27 In case of patients with head trauma, not severe to require a craniotomy, associated with thoracic injury, it was found that VATS can be performed effectively and safely with the advantage of shorter hospital stay and lesser infection when done within 4 days of trauma. 28 Thus, earlier the VATS, better is the success rate of evacuation and shorter is the hospital stay.…”
Section: Ideal Time To Perform Vatsmentioning
confidence: 99%